Analisis kerawanan longsor lahan di kabupaten majalengka provinsi jawa barat - Indrawati, Dewi Miska; , Dr. Kuswaji Dwi Priyono, M. Si (2016)
Landslide is one of the disasters that often happened and spreads even relatively in almost of the regions in Indonesia. Based to the data taken from Badan Penanggulangan Bencana Daerah (BPBD) of West Java Province in 2011 Majalengka Regency includes the regency of landslide insecurity. Landslide impact is very large, even, it can cause the dead of many people. Mapping the landslide insecurity area is needed to determine the distribution of the landslide insecurity area and minimize losses caused. The purpose of this research is to determine the dissemination of landslide insecurity in Majalengka regency and determine the dominant factor that causes landslide in the research area. The method which is used to analyze is GIS with a tiered quantitative method to reveal the maps of landslide insecurity. Each parameter is signed with dignity value. The parameter which are used in this research involve the utilization of the land, the slope, the rainfall obtained from the data of rainfall, soil type, and the earthquake zone/ground movement. The results of this research is map of landslide insecurity level in Majalengka Regency which divided into 4 class, those are the most insecure class of landslide which has 139,91 km2 (11,62%) of the research area,the insecure class of landslide which has 362,63 km2 (30,11%) of the research area, the less insecure class of landslide which has 561,56 km2 (46,63%) of the research area, and the secured class of landslide which has 140,14 km2 (11,64%) of the research area. The dominant factors which influences landslide in Majalengka is the soil types. The soil types in the research area is dominated the type of sensitive land. The types of sensitive land in the research area are regosol, litosol, latosol, yellow-red podsol, grumusol, and andosol. These soils has a loam sandy soil texture to the clay that causes extremely vurnerable to occur the landslide.